Knowledge and attitude towards the gradual reduction of salt in bread – an online survey - Costa, A. (2020)
Aim: Assess knowledge and attitude towards the gradual reduction of salt in bread and the potential impact on eating habits of children (6-18 years) and their families, as part as a Health Impact Assessment pilot study.